Teachers' Moral Evaluation of Students in an Inclusive Secondary School: A Study of Minority Students' Behaviour and School Performance - Mohammed-Awal Alhassan (Athens Institute for Education and Research, 2022)
This study aims to analyze the issue of morality in a teaching and learning set up. After discussion and answering the question "Is it ever the case that teachers hold students morally blameworthy or praiseworthy for factors that are known to be beyond their control?" the study concludes that teachers hold students to be morally blameworthy or praiseworthy for factors that are beyond their control, because they do not fully comprehend their lack of control over their situation, which is still bad. The study also found that most teachers do not have a clear cross-cultural knowledge of minority students' background causing a moral judgement dilemma of students' behaviours and actions. A critical look at other variables that may affect students' learning is recommended by this study.